Educational Innovation In Vocational Schools Humanistic-Religious Education Theory Perspective: The Use Of Vlogging As A Project-Based Learning Product - Hidayat, Didik Wahyu; Degeng, I Nyoman Sudana; Ulfa, Saida; Praherdhiono, Henry (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This article investigates the effectiveness of Project Learning (P.B.L.) and vlogging in network configuration learning at SMKN 2 Singosari, Malang, a humanist-religious educational theory perspective, focusing on improving the communication skills of grade XII TKJ students. The method used was the ASSURE development design, involving 34 students. The results show significant improvements in students' communication skills, providing empirical evidence of the benefits of integrating P.B.L. and vlogging in network engineering education. This research highlights the potential of innovative learning methods that combine theory and practice while strengthening essential competencies in the digital age and having the potential, freedom, and responsibility to develop themselves holistically, as well as being of faith, purity, and noble character.